TEMPERATURE EFFECTS ON THE STABILITY OF MYCOBACTERIUM TUBERCULO-SIS SHIKIMATE KINASE (MtSK): STRATEGIES FOR SECURE TRANSPORT - Wibowo, Aji; Komariyah, Tinta; Prabandari, Erwahyuni Endang; Ariyani, Titin; Siska, Eka (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2024)
Mycobacterium tuberculosis Shikimate Kinase (MtSK) has a crucial role in the shikimic pathway, which is essential for this bacteria but is absent in humans, making it a potential target for novel anti-tuberculosis drugs. This study used enzyme-coupled fluorescence to examine the stability of MtSK stored in 50% glycerol at -30 ℃, 4 ℃, and ±28 ℃ for six days. Results showed stable enzyme activity values (α=0.05) at all temperatures. This research underscores that MtSK’s stability depends on its molecular properties, including GC content, hydrophobic residues, Mg2+ binding, and intra-helical salt bridge. Despite some activity decline over time due to glycerol-induced aggregation, MtSK can be safely transported at ±28 ℃ for up to six days without special cooling compartment. Understanding MtSK stability ensures its active conformation remains consistent, reducing off-target effects on drug design and enhancing drug efficacy. This insight ultimately leads to high-quality and commercially viable tuberculosis treatment development. Future research should explore MtSK stability at higher temperatures and assess the optimal glycerol content for cryopreservation.